Medical Device Materials : Proceedings of the Materials and Processes for Medical Devices Conference 2009, August 10-12, 2009 Minneapolis, Minn., USA - Gilbert, Jeremy (Medical device materials, 2010)
This volume includes contributions from the world's foremost experts from academia, industry, and national laboratories involved in cardiac, vascular, neurological, and orthopaedic implants, dental devices, and surgical instrumentation/devices. Topics covered include: fabrication, fatigue, corrosion, tissue biocompatibility, cell-surface interactions, regulatory issues, shape memory alloys and a host of other cutting edge subjects. --